HUBUNGAN YANG SIGNIFIKAN ANTARA KEKUATAN OTOT LENGAN DAN BAHU DENGAN LONG SERVICE FOREHAND ATLET BULUTANGKIS PUTERA CLUB RTV PEKANBARU - Arie Waldi; Drs. Slamet, M.Kes, AIFO '; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Based on field observations when viewed Club Riau Televisionexercises are still many mistakes committed athlete Club Riau Television in completingmovement forehand long service. Starting from the time of taking the initial attitude, theprecision when doing long forehand service, the strength of the arm and shouldermuscles that have not been up to the time of service forehand long. The purpose of thisresearch is to look at the relationship of muscle strength of arms and shoulders with aprecision forehand long service Putera Club athletes RTV Pekanbaru. The populationin this study is the athletes Putera Club RTV Pekanbaru amounting to 8 people.Techniques of sampling using total sampling technique, where the entire population ismade in the sample. Data obtained from the dynamometer and expanding measurementcapabilities forehand long service. Data were analyzed using correlation producmoment. Based on the research that has been described in the previous chapter can bestated the conclusion that there is a significant correlation between the strength of armsand shoulders (X) with a long service forehand (Y) badminton athletes Putera Club RTVPekanbaru, obtained rhitung = 0.817> rtabel = 0.754 at α = 0.05.Keywords: Arm and Shoulder Muscle strength, long service forehand, and badminton.